Pupils' experience of noise in two acoustically different classrooms - Radun Jenni; Lindberg Mikko; Lahti Aleksi; Veermans Marjaana; Alakoivu Reijo; Hongisto Valtteri (EMERALD GROUP PUBLISHING LTD, 2025)
Purpose – This study aims to examine activity-related sound levels and pupils’ perceptions of the acoustic environment in two classrooms, one of which was a traditional classroom (Reference classroom, reverberation time (RT) 0.54 s) and the other a refurbished classroom (Demo classroom, RT 0.32 s).
Design/methodology/approach – Three types of data were gathered: room acoustic measurements, activity sound levels during different activities and pupils’ subjective experience concerning factors related to acoustics. Pupils, 10–11 years old (N = 34), estimated their subjective experience in general and after four test lessons. Teachers planned the test lessons to have four different lesson types: quiet work, one-person speaking, group work and activity-based work. The sound levels of activities were measured during the test lessons.
Findings – The activity sound levels were 2–13 dB LAeq lower in the Demo classroom than in the Reference classroom, depending on lesson type. Pupils were less annoyed by noise in the Demo than in the Reference classroom. Pupils’ speech was the most annoying sound source. More pupils were annoyed by it in the Reference classroom (65%) than in the Demo classroom (15%). Hearing the teacher while not seeing her face, concentrating on teaching and sitting in one’s place were estimated easier in the Demo classroom than in the Reference classroom.
Originality/value – This study offers a new approach using test lessons for studying activity sounds in schools. Activity sounds and their annoyance can be significantly diminished by classroom refurbishments.